Repair synthesis by human cell extracts in DNA damaged by cis- and trans-diamminedichloroplatinum(II). - Hansson, J (1989)
DNA damage was induced in closed circular plasmid DNA by treatment with cis- or trans-diamminedichloroplatinum(II). These plasmids were used as substrates in reactions to give quantitative measurements of DNA repair synthesis mediated by cell free extracts from human lymphoid cell lines. Adducts induced by both drugs stimulated repair synthesis in a dose dependent manner by an ATP-requiring process. Measurements by an isopycnic gradient sedimentation method gave an upper limit for the average patch sizes in this in vitro system of around 140 nucleotides. It was estimated that up to 3% of the drug adducts induce the synthesis of a repair patch. The repair synthesis is due to repair of a small fraction of frequent drug adducts, rather than extensive repair of a rare subclass of lesions. Nonspecific DNA synthesis in undamaged plasmids, caused by exonucleolytic degradation and resynthesis, was reduced by repeated purification of intact circular forms. An extract made from cells belonging to xeroderma pigmentosum complementation group A was deficient in repair synthesis in response to the presence of cis- or trans-diamminedichloroplatinum(II) adducts in DNA.